ASUHAN KEPERAWATAN PADA KLIEN STROKE DENGAN MASALAH GANGGUAN MOBILITAS FISIK - Riyan Maysanto (2023)
Background : Strock is a neurological disease that occurs suddenly and causes a total blockage or blockage of portion of the blood vessels in the brain within apporximately 24 hours. Non-hemorrhagic stroke is that most common type of pathology, which accounts for 80% of all non-hemorrhagic strokes, divided There are 3 types of stroke, namely, thrombolytic stroke, embolic stroke and systemic hypoperfusion.Research method : This study uses a qualitative descriptive method with a case study approach. Research results : The results of this study found that the main nursing problem was impaired physical mobility. The main nursing action that is applied is Range Of Motion (ROM) exercise. The nursing evaluation is partially resolved with the goals and outcome criteria set. Conslusion : The application of nursing care to stroke clients with impaired physical mobility achieves the expected results due to good cooperation between nurses, patients and social care workers.